Determination of psychosocial, personality traits, lifestyles factors and weight status among students in a public university in Malaysia - Suhaimi, Nurul Fareeza (2020)
The escalating prevalence of overweight and obesity (OW-OB) among university students is a continuous concern. OW-OB raised a public attention as it is considered as one of the risk factors towards development of non-communicable disease including hypertension, cardiovascular disease and diabetes mellitus. A cross-sectional study was conducted to determine prevalence and factors associated with OW-OB among Universiti Putra Malaysia (UPM) students. Selfadministered questionnaires were used to determine sociodemographic background, psychosocial, personality traits, lifestyle factors and weight status. The psychosocial factors consist of self-esteem and social support were determined using Rosenberg Self-Esteem Scale (RSES) and Multidimensional Scale of Perceived Social Support (MSPSS) respectively. Personality traits were assesed using USM Personality Inventory (USMaP-I). Lifestyle factors assesed physical activitiy and sleep quality using Global Physical Activity Questionaire (GPAQ) and Pittsburgh Sleep Quality Index (PSQI) respectively. Dietary factors were assessed by Eating Behaviour Questionaires (EBQ) and Diet Quality Index- Revised (DQI-R). Assesment of nutritional status included measurement of anthropometry included (height, weight, waist circumference, body fat percentage and visceral fat), biochemical data (fasting lipid profiles, fasting blood glucose) and blood pressure. Clinical data on blood pressure were measured using a digital sphygmomanometer. A total of 240 undergraduates (24.6% male and 75.4% female) with mean (±SD) age of 21.22±1.24 years were recruited from four randomly selected faculties in UPM. The classification of body weigh status of the respondents indicated that 61.3% had normal weight, 12.9% underweight and 19.6% overweight and 6.3% obese. The prevalence of OW-OB were 25.9% vs 74.1% normal and underweight (UW-NW). Majority of respondents were Malay (79.2%) and mostly resided in hostel (95%). More than half of the respondents received adequate social support from their social circles; mainly from significant other (52.5%), family (68.8%) and friends (56.7%) respectively. Personality traits shows majority of the respondents were having neuroticism (76.2%), openness (59.0%) and conscientiousness (61.5%) traits. Almost two – thirds (65.8%) from total respondents were categorized under moderate physical activity level however, half (50.4%) of them experienced poor sleep quality. Results on eating behaviour indicated that 42.5% of respondents skipped at least one main meal per day where breakfast (77.9%) was the most frequently skipped meal. More than half (53.3%) ate at western fast food restaurant 1-3 times per months. Overall mean DQI-R was 58.38±13.18 suggested in need of improvement. Average score (±SD) of the self-esteem was 18.29±4.67 which indicates respondents had moderate self-esteem. Prevalence of abdominal obesity were 11.3%, 47.9% having high body fat percentage and 7.5% were having high visceral fat level. Assessment of biochemical and clinical data show 26.3% were at risk level for total cholesterol (TC), 3.8% at risk level for triglycerides (TG), 2.1% had low HDL and 60.4% of respondents had at risk level for LDL. All of the respondents had optimal blood glucose level. For blood pressure, about 14.2% and 10.0% from total respondents were at risk level for systolic and diastolic. Compare across body weight status, OW-OB significantly having lower selfesteem (p<0.05), experienced poorer sleep quality (p<0.05), skipped more main meal (p<0.05), having higher mean of waist circumference (81.70±7.77cm) (p<0.05), higher mean of body fat (33.10±5.45) and visceral fat (8.40±3.39) (p<0.05), higher mean of TC (4.97±0.67), TG (1.00±0.61), LDL (3.04±0.56), lower HDL (1.47±0.27) (p<0.05) and higher mean for systolic (113.12±13.04) and diastolic (73.98±8.76) blood pressure (p<0.05) compared to UW-NW counterparts. OW-OB also found to have higher social support in all domains, have predominant personality traits of conscientiousness (8.28±1.95), extraversion (9.29±1.89) and agreeableness (9.04±1.67) and higher engagement in physical activity (67.7%) and poorer diet quality however, these association were too small to be significant. Multivariate logistic regression indicates that the odds of being OW-OB were five times likely if respondents had high LDL level (OR=5.08, CI=1.29-20.11, p<0.02) and frequent skipping meals (OR=4.97, CI=1.06-23.38, p<0.04), three times likely if respondents had high triglycerides (OR=2.55, CI=1.10-5.95, p<0.03) and twice likely if respondents had poor sleep quality (OR=2.10, CI=1.09-4.05, p<0.03). Higher diastolic blood pressure (OR=1.08, CI=1.03-1.12, p<0.001) increased chances of respondents being OW-OB compared to normotensive respondents. As a conclusion, this study found university students with poor sleep quality frequently skipped meals with poor fasting lipid profiles and elevated blood pressure were at higher risk to be OW-OB. This study highlights the importance of conducting healthy lifestyle and having healthy body weight by modify the modifiable lifestyle behaviour by having good sleep quality, and eating behaviours to improve lipid profiles and blood pressure.